2020
DOI: 10.2196/19464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transmissibility of Coronavirus Between Symptomatic and Asymptomatic Patients: Reanalysis of the Ningbo COVID-19 Data

Abstract: Background Since the outbreak of the novel coronavirus disease (COVID-19) in December 2019, the coronavirus has spread all over the world at an unprecedented rate. The transmissibility of the coronavirus from asymptomatic patients to healthy individuals has received enormous attention. An important study using COVID-19 data from the city of Ningbo, China, was carried out to estimate and compare the transmission rates of the coronavirus by the symptomatic and asymptomatic patients. However, in the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…There is a great interest in the detection of SARS-CoV-2 infection in asymptomatic patients, as they can contribute to the viral spread with similar transmission rates as symptomatic patients [15]. There is numerous emerging evidence of patients affected by COVID-19 pneumonia who are asymptomatic or mildly symptomatic at the time of the diagnosis who show imaging features consistent with lung involvement, similarly to the case report we presented [16,17].…”
Section: Discussionsupporting
confidence: 71%
“…There is a great interest in the detection of SARS-CoV-2 infection in asymptomatic patients, as they can contribute to the viral spread with similar transmission rates as symptomatic patients [15]. There is numerous emerging evidence of patients affected by COVID-19 pneumonia who are asymptomatic or mildly symptomatic at the time of the diagnosis who show imaging features consistent with lung involvement, similarly to the case report we presented [16,17].…”
Section: Discussionsupporting
confidence: 71%
“…Viral transmission by asymptomatic carriers has also been reported in many studies (Bai et al 2020 ; Hu et al 2020c ; Lavezzo et al 2020 ; Qian et al 2020b ; Rothe et al 2020 ; Tong et al 2020 ). Some investigations indicate transmission rates by asymptomatic patients are as high as symptomatic patients (Chen et al 2020 ; Yin and Jin 2020 ) while others estimate the rate as one third of that of symptomatic transmissions (Wu 2020 ). Indeed, there is no significant difference in viral load between asymptomatic and symptomatic groups (Zou et al 2020 ) while the asymptomatic group shed virus significantly longer than the symptomatic group (Long et al 2020 ).…”
Section: Shedding Of Sars-cov-2mentioning
confidence: 99%
“…Chen et al ( 36 ) followed up and investigated 2,147 close contacts in Ningbo, Zhejiang, China, with a total infection rate of 6.15%, while there was no significant difference in the infection rate between the confirmed cases and asymptomatic cases (6.30 and 4.11%, respectively) ( 36 ). Concomitantly, Yin and Jin ( 37 ) analyzed the transmission rate of 157 symptomatic cases and 30 asymptomatic cases of COVID-19 and identified that there was no significant difference in the transmission rate between symptomatic and asymptomatic patients. However, none of these studies excluded pre-symptomatic patients in the incubation period.…”
Section: Infectivity and Transmission Risk Of Asymptomatic Carriermentioning
confidence: 99%